Just a song Chinese lyrics from the eleventh and early twelfth centuries - Owen, Stephen 1946- (Harvard University Asia Center, 2019)
"Analyzes the transformation of song lyric (ci), a form of Chinese poetry, from performance contribution to a full literary genre. Examines its discursive contrast to older classical poetry, as well as its emphasis on sensibility, which was lost in the new Song world of righteousness and public advancement"...Provided by publisher
Includes bibliographical references and index
Keywords: Shi, Su -- 1164-1222; Su, Shi -- 1037-1101; Geschichte 1000-1150; Chinese poetry -- Song dynasty, 960-1279 -- History and criticism; Performance poetry -- China -- History; Chinesisch; Ci; China -- Civilization -- 960-1644